Analisis Keterpaparan Informasi Kesehatan Reproduksi Remaja di Panti Asuhan - Jumiatun; Pujiati Setyaningsih (Nur Science Institute, 2022)
In line with the swift currents of globalization that hit various sectors and joints of life, adolescent reproductive health problems have also developed. One of the causes of the problem, possibly because of ignorance, as a result of adolescents not getting clear, correct and precise information about adolescent reproductive health and its problems. Information about reproductive health is still widely accessed on the internet, even though the truth of the sites that provide reproductive health information on the internet is not necessarily the truth. There needs to be justification from parties who really understand reproductive health, both from parents, teachers, health workers, and so on. The purpose of this study was to analyze the exposure to information about adolescent reproductive health in orphanages. This study uses a descriptive approach, the sample is taken in total, data collection using a questionnaire. The results showed that the majority of respondents were aged 13-16 years, but some had not been exposed to information about reproductive health which included puberty, pregnancy and sexually transmitted diseases. The majority of information exposure on reproductive health comes from teachers (72%) and health workers (37%), while the media as the most common source of information are the internet (45%), books (45%) and social media (42%).